Medical Image Processing, Human Face Classification, Face Recognition and Medical Imaging: Performance Evolution Histogram of Orientation Gradients (Indian Journal of Forensic Medicine & Toxicology, 2021)
In view of the common conditions and the security of the country from all the blackmail that is urging, whetheron the level of the Internet and social communication, there was an urgent need to secure all institutions andalso secure our phones and our possessions from laptops and others using more accurate safety methodsthan these methods I used the method of destination classification, i.e. identifying the destination so that it ispossible to secure We can see you through the fingerprint of the destination, and this method that is popularrecently. In this paper, HoG algorithm was used and this algorithm is considered one of the powerful waysto extract the features that we need in the classification process relying on one of the methods of learning amachine an algorithm was used naive Bayes. After that, the system is evaluated by calculating the accuracy,specificity, and sensitivity and it is found that the efficiency of the system reaches 98%.
Keywords: HoG, Naïve bayes, Bilateral Filter, histogram equalization.